Application of supporting construction technology for deep foundation pit in Building Foundation Engineering. Issue 1 (June 2021) - Zhang, Zhuan; Zhang, Sheng; Lu, Siming
Abstract: This paper discusses and analyzes the Construction Technology of deep foundation pit support in foundation engineering. This paper is based on a residential district project in southern Jiangxi Province, this paper expounds the theoretical definition, basic requirements, construction standards, several common construction techniques of deep foundation pit support and the suggestions and ideas of foundation engineering construction. This paper tries to provide a theoretical reference for the enterprises and workers involved in the construction of foundation engineering.